A study of renal dysfunction among HIV-infected patients on tenofovir based ART regimen in the Northeast part of India - Gayatri, Lourembam; Manpang, Nang N.; Nobing, Duyu; Chongtham, Dhanaraj S.; Singh, M. Bijoy; Mazumdar, Sudhangshu (International Journal of Advances in Medicine, 2020)
Background: Tenofovir is an integral part of the currently used antiretroviral therapy (ART) regime. However, nephrotoxicity has been a concern. This study has been undertaken to evaluate the prevalence and risk factors of renal dysfunction among HIV-patients on tenofovir containing ART regime. Methods: This cohort study was conducted at Regional Institute of Medical Sciences. HIV-patients newly started on tenofovir containing ART regime were subjected to detailed history, thorough physical examination, and routine investigations. Serum creatinine levels and creatinine clearance were measured at regular intervals. Results: Mean age of the patients was 42.37±10.8 years. Most of the patients had normal BMI (66%) and 22% were obese while 12% of the cases were underweight. Majority of the patients had CD4 count less than 350 cells/cumm. Renal dysfunction, defined as creatinine clearance <50 ml/min, developed in 9% of the patients at 3 months and in 33% of the patients at 6 months. Old age, low CD4 cell count, HCV co-infection, and advanced HIV infection were found to be important risk factors. Conclusions: Development of renal dysfunction is common among HIV patients receiving tenofovir-based ART regimen. Old age, low CD4 cell count, HCV co-infection, and advanced HIV infection were found to be important risk factors.